Gamification Enhanced Micro Learning in Blended Learning: Effects on Knowledge and Skills - Disa, Syaharullah; Sitti Arni (Pusat Penelitian dan Pengabdian Pada Masyarakat Sekolah Tinggi Manajemen Informatika dan Komputer AKBA Makassar, 2025)
Innovative learning approaches are essential to address 21st-century educational challenges and enhance learner engagement. This study examines the impact of integrating gamification into micro-learning to improve student knowledge and skills within blended learning environments. A quasi-experimental design assigned 56 students to either a treatment group, which used an Android application featuring gamification and micro-learning principles, or a control group, which received conventional instruction. T-test results indicated a significant post-intervention improvement in knowledge and skills for the treatment group (t = -17.352, p < 0.001) compared to the control group (t = -7.402, p < 0.001). An independent t-test also showed a significant difference between the groups' final results (p < 0.001), with the treatment group averaging 91.96 and the control group 78.87 on the post-test. These findings demonstrate that gamification-enhanced micro-learning can increase student motivation, engagement, and critical thinking and problem-solving skills. The study underscores the important role of educators as facilitators who connect play-based experiences with meaningful learning outcomes.